Developing the Ability to Read the Qur'an With Rhythm (Tilawah Al-Qur'an) at Sanggar Guidance Segambut, Kuala Lumpur Malaysia - Ahmad Zaki; Muhammad Alfikri Ananda; Said Rasyid Habibi (International Journal of Islamic Educational Research, 2025)
Recitation of the Qur'an is the art of reading the Qur'an with beautiful tartil and rhythm, which has been developed in the Islamic tradition for centuries. This study aims to review the concept of recitations, the history of its development, as well as the implementation of the art of reading the Koran in learning at Sanggar Guidance Segambut, Kuala Lumpur, Malaysia. The recitation program implemented at the Segambut Guidance Studio focuses on mastering maqamat (tones) and systematic tartil training. With this approach, students find it easier to understand the rules of recitation and have the skills to recite holy verses beautifully and correctly.